Auditory Neuropathy as the Initial Phenotype for Patients With ATP1A3 c.2452 G > A: Genotype–Phenotype Study and CI Management - Wang, Wenjia; Li, Jin; Lan, Lan; Xie, Linyi; Xiong, Fen; Guan, Jing; Wang, Hongyang; Wang, Qiuju (Frontiers in Cell and Developmental Biology, 2021)
Objective: To analyzse the genotype-phenotype correlation of patients with Auditory neuropathy (AN), which is a clinical condition featuring normal cochlear responses and abnormal neural responses, and ATP1A3 c.2452 G>A (p.E818K), which has been generally recognized as a genetic cause of CAPOS (cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss) syndrome. Methods: Four patients diagnosed as AN by clinical evaluation and otoacoustic emission and auditory brainstem responses were recruited, and analyzsed by next-generation sequencing to identify the candidate disease-causing variants. Sanger sequencing were was performed on the patients and their parents to verify the resultresults and short tandem repeats -based testing was conducted to confirm the biological relationship between the parents and the casescasepatients. Furthermore, cochlear implantation (CI) was performed in one AN patient to reconstruct hearing. Results: Four subjects with AN were identified to share a de novo variant, p.E818K in the ATP1A3 gene. Except for the AN phenotype, patient 1 and 2 exhibited varying degrees of neurological symptoms, implying that they can be diagnosed as CAPOS syndrome. During the 15 -year’s followingfollow-ing up of patient 1, we observed delayed neurological events and a progressive bilateral sensorineural hearing loss in PTA. Patient 2 underwent CI on his left ear, and with the result wasbeing poor. The other two patients (patient 3 and patient 4, who was were 8 and 6 years old, respectively), contrastingly, denied any neurological symptoms. Conclusion: ATP1A3 p.E818K has rarely been documented in the Chinese AN population. Our study confirms that p.E818K in the ATP1A3 gene is a mMulti-ethnic cause of AN in Chinese individuals. Our study further demonstrates the significance of genetic testing for this specific mutation , p.E818K, for identificationidentifyingication of the special subtype of AN with somewhat favorable CI outcome and offers a more accurate genetic counseling about the specific de novo mutation.